Meclozine Attenuates the MARK Pathway in Mammalian Chondrocytes and Ameliorates FGF2-Induced Bone Hyperossification in Larval Zebrafish - Takemoto, Genta; Matsushita, Masaki; Okamoto, Takaaki; Ito, Toshinari; Matsuura, Yuki; Takashima, Chieko; Chen-Yoshikawa, Toyofumi Fengshi; Ebi, Hiromichi; Imagama, Shiro; Kitoh, Hiroshi; Ohno, Kinji; Hosono, Yasuyuki (Frontiers in Cell and Developmental Biology, 2022)
Meclozine has been developed as an inhibitor of fibroblast growth factor receptor 3 (FGFR3) to treat achondroplasia (ACH). Extracellular signal regulated kinase (ERK) phosphorylation was attenuated by meclozine in FGF2-treated chondrocyte cell line, but the site of its action has not been elucidated. Although orally administered meclozine promoted longitudinal bone growth in a mouse model of ACH, its effect on craniofacial bone development during the early stage remains unknown. Herein, RNA-sequencing analysis was performed using murine chondrocytes from FGF2-treated cultured tibiae, which was significantly elongated by meclozine treatment. Gene set enrichment analysis demonstrated that FGF2 significantly increased the enrichment score of mitogen-activated protein kinase (MAPK) family signaling cascades in chondrocytes; however, meclozine reduced this enrichment. Next, we administered meclozine to FGF2-treated larval zebrafish from 8 h post-fertilization (hpf). We observed that FGF2 significantly increased the number of ossified vertebrae in larval zebrafish at 7 days post-fertilization (dpf), while meclozine delayed vertebral ossification in FGF2-induced zebrafish. Meclozine also reversed the FGF2-induced upregulation of ossified craniofacial bone area, including ceratohyal, hyomandibular, and quadrate. The current study provided additional evidence regarding the inhibitory effect of meclozine on the FGF2-induced upregulation of MAPK signaling in chondrocytes and FGF2-induced development of craniofacial and vertebral bones.